Indian gold jewellery industry : culture and consumption - Raha, Sylvia (Routledge, 2024)
"India has a long-standing cultural and societal affinity with gold and gold jewellery. Gold metaphorically represents the sacredness, purity and immortality that bind religious beliefs and culture together. Accumulation of gold is associated with material and non-material cultures where the perceptions, attitudes and experiences of the members engaged in production and consumption are bound into a complex relationship. The idea of the book initially originated from the course of research work. It was found that India has the largest unorganised jewellery industry, in terms of manufacturing and consumption unit. Jewellery fabrication in India is not just a profession for the jewellers but it has been a family tradition extending across the generations. Gold jewellery makers (sunnar, swarnakars) are the spine of the jewellery industry. They acquired the skill of making jewellery from the experienced and learned gold smithery (karigars), either from their ancestors who were engaged in this business or from the craftsmen-cum-petty traders. The co-relations of castes, religion, culture, economy and class are intertwined with each other in such a way that made the gold jewellery industry sustainable. Surprisingly, there is an absence of literature on understanding the structural and functional aspects of the gold jewellery industry in India. This book explores the roles of sunars/ swarnakars (goldsmith or jewellery makers), consumers, trade and the policies that bring a change in the gold jewellery industry in India and India's position in the global market scenario. By focusing on their way of life, the book brings unique insights into the social and economic experience of the unorganised gold jewellery sector and the role of consumers in production"-- Provided by publisher.
Keywords: Jewelry trade -- India.; Gold jewelry -- India.; Gold industry -- India.; elektronické knihy; electronic books